2020
DOI: 10.1002/anie.201912312
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Based Nanoengineered Pharmacokinetics of Iron‐Doped Copper Oxide for Nanomedical Applications

Abstract: The progress in nanomedicine (NM) using nanoparticles (NPs) is mainly based on drug carriers for the delivery of classical chemotherapeutics.A sl ow NM delivery rates limit therapeutic efficacy,a ne ntirely different approach was investigated. Ahomologous series of engineered CuO NPs was designed for dual purposes (carrier and drug) with adirect chemical composition-biological functionality relationship. Model-based dissolution kinetics of CuO NPs in the cellular interior at post-exposure conditions were contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…In a recent work from our group, we show that Cu 2+ released from CuO dissolution tend to complex with various amino acids and form light blue precipitates in glutamine solutions in the ratio 1 : 2, as conrmed using single-crystal X-ray diffraction (SC-XRD). 79 These ndings are in line with previously reported structural formations between Cu 2+ and glutamine. 112 In fact, several early works have described the crystal structure that results from Cu 2+ complexation with various amino acids, such as asparagine, 113 glutamic acid 114 and aspartic acid.…”
Section: Oxidative Stress Due To M Z+ Release From Inorganic Nps As Main Cause Of Toxicitysupporting
confidence: 92%
See 2 more Smart Citations
“…In a recent work from our group, we show that Cu 2+ released from CuO dissolution tend to complex with various amino acids and form light blue precipitates in glutamine solutions in the ratio 1 : 2, as conrmed using single-crystal X-ray diffraction (SC-XRD). 79 These ndings are in line with previously reported structural formations between Cu 2+ and glutamine. 112 In fact, several early works have described the crystal structure that results from Cu 2+ complexation with various amino acids, such as asparagine, 113 glutamic acid 114 and aspartic acid.…”
Section: Oxidative Stress Due To M Z+ Release From Inorganic Nps As Main Cause Of Toxicitysupporting
confidence: 92%
“…Similarly, the homeostasis of Cu 2+ is maintained by Cu importers such as CTR1 and ATPase that respectively increase or decrease the ux of Cu 2+ within the cell. 78,79 When the level of intracellular Cu 2+ is increased beyond normal conditions, CTR1 is internalized while ATPase is transferred to the cell membrane to eliminate the excess ions. However, during cellular uptake and subsequent dissolution of CuO NPs, the release of Cu 2+ is signicantly higher and more rapid than the capacity of ATPase to excrete the excess ions, disrupting the redox balance and inducing ROS generation and oxidative stress.…”
Section: Oxidative Stress Due To M Z+ Release From Inorganic Nps As Main Cause Of Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…[49,126] In addition, CuO, NiO, Ag NPs, and quantum dots displayed significant dissolution in biological media and animal tissues. [127][128][129][130][131][132][133][134] While endocytosis is the major cellular internalization pathway for most ENMs, NPs may transport into an acidic and enzymatic lysosomal compartment. [19,33] Therefore, a majority of metal-based NPs may display rapid dissolution after cellular internalization.…”
Section: Decompositionmentioning
confidence: 99%
“…Furthermore, reinjecting the tumour cells to the same mice did not generate a new tumour suggesting the successful induction of long term immune memory response. 235 Recently, Ploetz E. et al, demonstrated that hybrid metalorganic framework (MOF) nanoparticles loaded in liposomes (Lip-MOFs) could create a controllable platform for intracellular iron delivery. The high amount of realized ions by the internalized particles induced pyroptosis, a highly inammatory form of programmed cell death, which occurred only in slightly acidic extracellular environments.…”
Section: Immunogenic Cell Death Inductionmentioning
confidence: 99%